Is the coast clear? Trust, risk-reducing behaviours and anxiety toward cruise travel in the wake of COVID-19 - Quintal, Vanessa; Sung, Billy; Lee, Sean (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The study develops a segmentation typology based on consumer trust toward a particular agency and explores the impacts risk-reducing behaviours and anxiety have on cruise travel in the wake of COVID-19. It examined 504 Australian respondents in an online survey to derive three consumer segments, namely, Trust Government, Trust Government, and Cruise Company and Trust None. All three segments demonstrated that reduced anxiety significantly heightened desire and subsequently, intention to travel. The conceptual contributions of integrating trust, handled risk and anxiety in the crisis travel literature were highlighted. Also, the pragmatic implications for addressing trust to reduce risk and anxiety as well as to increase desire and intention to travel were examined with a proposed 4Cs framework.